PENANGANAN DAN PENERAPAN TEKNOLOGI PASCAPANEN TANAMAN OBAT - Harto Widodo; Dyah Subositi (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Post-harvest handling of medicinal plants (MP) is an important process for providing medicinal materials which either directly used as a simplicia or further processed products. Improper handling will deteriorate the physical, chemical and biological (microbial contamination) quality of simplicia. Otherwise, the appropriate process will achieve good quality products especially the target active constituents of medicinal plants that can be maintained, or even increased. The purpose of this paper was to discuss the important aspects of postharvest management and the application of technology to reduce the loss of quality and quantity of medicinal plant yields. The post-harvest process of medicinal plants generally includes the stages of fresh sorting, washing, draining, cutting, drying, dry sorting, packaging and storing. The principle of postharvest handling of medicinal plants must be based on obtaining the product with the lowest possible cost, water content, energy consumption, space, and resources, and with the highest physical, chemical, and biological quality. The best postharvest handling methods for one medicinal plant cannot be generally applied to other medicinal plants. Proper post-harvest technologies should be developed for an individual MP to achieve quality products. Comprehensive research on postharvest handling process is needed for individual MP commodity based on the characteristics of each ingredient and the target of active principles so that the most suitable method for each type of medicinal plant is obtained.